Governing expectations of forensic innovations in society: the case of FDP in Germany - Nunes, Nina Amelung (2021)
This article is about the governance of expectations of forensic DNA phenotyping (FDP) innovations in Germany used for the prediction of human externally visible traits such as eye, hair, and skin color, as well as biological age and biogeographic ancestry. In 2019, FDP technologies were regulated under the label “extended DNA analysis”. We focus on the expectations of members of the forensic genetics’ community in Germany, in anticipation and response to those of regulators who advocated for such technologies. Confronted with regulators’ expectations of omnipotent technologies and the optimistic promise that they will enhance public security, forensic geneticists responded with attempts to adjust such expectations, specifying limits and risks, along with a particular logic sorting matters of concern. We reflect on how forensic geneticists’ govern expectations through forms of distributed anticipatory governance, delimiting their obligations, and distributing accountability across the criminal justice system.